(untitled) (Italian Journal of Public Health, 2010)
Giuseppe La Torre has, in his manual “Applied Epidemiology and Biostatistics”, drawn upon his experience (long and intense despite his young age) as applied epidemiology expert in the Catholic University of Sacred Heart. For some years, in fact, he has offered valuable advice to many researchers who had failed to publish in international journals because of an inappropriate use of epidemiological methods and biostatistics, and has helped many of them present the results of their research. After numerous rejected papers, researchers would turn to his expertise and knowhow of the most modern epidemiological tools. The results were flattering: the papers which Professor La Torre and his staff had dealt with the epidemiological issues, as if by magic, were accepted for publication. It is therefore justified and understandable that the author has decided to propose, to a wider public, his epidemiological expertise about applied epidemiology. But there is no magic. The author simply focuses on the need to apply epidemiological methods to areas of public health practice for determining disease etiology and the “real-life” applications to public health and health services research.